Analysis on the Relation of Contraception Selection Towards Perceptions of Side Effects in Couples of Reproductive Age in the Working Area of Lubuk Buaya Public Health Center in Lubuk Buaya Sub-District, Padang City - Sandra Ilona; Nuzulia Irawati; Aladin Aladin (Science Midwifery, 2021)
Family Planning Program (KB) is one of the programs used to cope with the increasing population. The purpose of the Family Planning Program (KB) is to improve the quality of the population through birth control, to reduce mortality, and to improve the quality of the family planning program, one of which is by using the Long-Term Contraceptive Method (MKJP). Side Effects on Couples of Reproductive Age in the Working Area of the Lubuk Buaya Public Health Center, Lubuk Buaya Sub-district, Padang City.This study used a cross sectional design. The research population was all couples of reproductive age who were in the working area of the Lubuk Buaya Sub-district Public Health Center, Padang City who received contraceptive services. The sample of this study was 108 respondents of reproductive age couples who had received family planning services. Data were collected by using questionnaires and data were analyzed by using chi-square test and logistic regression test. The results of this study found that there was a significant relation between perceptions of side effects on the contraception selection (p = 0.016) The conclusion of this study is that there is a relation between perceptions of the side effects on contraception selection.